What moves patients to participate in prehabilitation before major surgery? A mixed methods systematic review - Miriam van der Velde; Marike van der Leeden; Edwin Geleijn; Cindy Veenhof; Karin Valkenet (BMC, 2023)
Abstract Background Prehabilitation offers patients the opportunity to actively participate in their perioperative care by preparing themselves for their upcoming surgery. Experiencing barriers may lead to non-participation, which can result in a reduced functional capacity, delayed post-operative recovery and higher healthcare costs. Insight in the barriers and facilitators to participation in prehabilitation can inform further development and implementation of prehabilitation. The aim of this review was to identify patient-experienced barriers and facilitators for participation in prehabilitation. Methods For this mixed methods systematic review, articles were searched in PubMed, EMBASE and CINAHL. Articles were eligible for inclusion if they contained data on patient-reported barriers and facilitators to participation in prehabilitation in adults undergoing major surgery. Following database search, and title and abstract screening, full text articles were screened for eligibility and quality was assessed using the Mixed Method Appraisal Tool. Relevant data from the included studies were extracted, coded and categorized into themes, using an inductive approach. Based on these themes, the Capability, Opportunity, Motivation, Behaviour (COM-B) model was chosen to classify the identified themes. Results Three quantitative, 14 qualitative and 6 mixed methods studies, published between 2007 and 2022, were included in this review. A multitude of factors were identified across the different COM-B components. Barriers included lack of knowledge of the benefits of prehabilitation and not prioritizing prehabilitation over other commitments (psychological capability), physical symptoms and comorbidities (physical capability), lack of time and limited financial capacity (physical opportunity), lack of social support (social opportunity), anxiety and stress (automatic motivation) and previous experiences and feeling too fit for prehabilitation (reflective motivation). Facilitators included knowledge of the benefits of prehabilitation (psychological capability), having access to resources (physical opportunity), social support and encouragement by a health care professional (social support), feeling a sense of control (automatic motivation) and beliefs in own abilities (reflective motivation). Conclusions A large number of barriers and facilitators, influencing participation in prehabilitation, were found across all six COM-B components. To reach all patients and to tailor prehabilitation to the patient's needs and preferences, it is important to take into account patients' capability, opportunity and motivation. Trial registration Registered in PROSPERO (CRD42021250273) on May 18th, 2021.